Exercise is medicine for depression: even when the “pill” is small - Hallgren M; Vancampfort D; Stubbs B (Neuropsychiatric Disease and Treatment)
Mats Hallgren,1 Davy Vancampfort,2,3 Brendon Stubbs4,5 1Department of Public Health Sciences, Karolinska Institutet, Stockholm, Sweden; 2Department of Rehabilitation Sciences, 3University Psychiatric Centre – KU Leuven, KU Leuven – University of Leuven, Leuven, Belgium; 4Department of Physiotherapy, South London and Maudsley NHS Foundation Trust, 5Department of Health Service and Population Research, Institute of Psychiatry, Psychology and Neuroscience, King’s College London, London, UK In a recent perspectives article, Gerber et al argue persuasively that more systematic efforts are needed to utilize the considerable treatment potential of exercise in psychiatric care. Specifically, the authors highlight the inherent difficulties that clinicians and researchers face when encouraging patients to initiate and maintain a regular physical activity program. These obstacles relate to dysfunctional cognitive–emotional processes which, the authors argue, can interfere with patients’ capacity to self-regulate health-related behaviors such as exercise. View the original article by Gerber et al